REHABILITATION SANCTIONS AGAINST THE NARCOTICS USER ACCORDING TO THE PERSPECTIVE OF MAQASHID SHARIAH - Andriyani, Andriyani; Dewi, Rusmala (Nurani, 2020)
The government through the law makes a policy to aggressively seek rehabilitation for the drug users. This is done in the context of tackling the abuse of narcotics in Indonesia. Thus, it is necessary to study the policy objectives based on the perspective of maqashid sharia by conducting qualitative research using secondary data. From the results of the research, the Indonesian Government has implemented rehabilitation sanctions for the narcotics user because the users are victims of other people's crimes, namely illegal narcotics dealers. If a narcotics user is given a sanction of imprisonment / imprisonment, it will have a worse impact and cannot eliminate his dependence on narcotics. Seen from the perspective of maqashid sharia, this government policy does not conflict with the objectives contained in the maqashid sharia concept, as the goal of rehabilitation which requires the users to be aware of their mistakes, so that they will become better humans both towards their God and those around him.